Dynamics and perceptions of social support and their impact on well-being: a qualitative study of adolescents in Northern Ghana. Issue 5 (19th October 2016) - Wilson, Angelina; Somhlaba, Nceba Z.
Abstract: Although perceived social support has been studied in various contexts, there is still scant research on qualitative accounts of how perceptions of support for adolescents living in impoverished contexts are formed and relate to psychological well-being. We explored the dynamics and perceptions of social support among 18 purposefully selected school-going adolescents in the northern region of Ghana. Emerging thematic areas comprised: the dynamics of familial networks that included quality familial relationships; valued support from friends; and the negative aspects of various social relations. With family – and peer social relations perceived as beneficial for practical advice and – support, the mere existence of social ties was not the adolescents' most important consideration for well-being. Instead, the quality of interactions across different social networks emerged as more instrumental for relational and overall well-being. Understanding the sources of problematic social interactions, such as the consideration of 'face-saving' when seeking instrumental support, could provide useful suggestions for interventions aimed at creating social environments that enhance positive mental health.